ASSESSING PRISON HEALTH CARE IN PAKISTAN: A LEGAL PERSPECTIVE - Niaz Mustafa; Smia Mukhtar; Muhammad Haris (International Journal of Contemporary Issues in Social Sciences, 2024)
The health care system in prisons is an essential component of public health and human rights. In Pakistan, the prison health care system faces numerous challenges, including inadequate medical facilities, lack of trained medical staff, and insufficient legal frameworks to ensure the health rights of inmates. This research article provides an in-depth legal perspective on assessing prison health care in Pakistan. The study meticulously examines existing laws, policies, and their implementation, while also evaluating the health care conditions and services provided to prisoners. Specifically, the analysis focuses on the Pakistan Prison Rules 1978, the Constitution of Pakistan, The Prisoners Act, Regulation II and Confinement of State Prisoners, Book -1 of The Prison Code Rules for superintendence and management of prisons in Pakistan, and international treaties like the International Covenant on Economic, Social and Cultural Rights (ICESCR). Despite these mandates, enforcement is often lacking, resulting in significant disparities between legal standards and actual conditions. This study adopts a mixed-methods approach, combining qualitative and analytical research methodologies, including legal analysis and fieldwork, to provide a comprehensive assessment of prison health care in Pakistan from a legal perspective. The findings reveal substantial gaps between legal provisions, practical enforcement, and preventive health care measures. The article concludes with recommendations for policy reforms and improved legal mechanisms to enhance the prison health care system in Pakistan. This study highlights the need for robust legal frameworks and their stringent implementation to ensure that the health rights of prisoners are upheld in accordance with international human rights standards, offering novel insights into potential legal and policy improvements.